Mediation Effect of Resilience Between Social Support and Depression Symptoms in Patients With Strabismus: A Cross-Sectional Study [Corrigendum] - Mo Y; Zhang H; Yu X; Xu Z; Xiao H; Gao L; Wang Y (Journal of Multidisciplinary Healthcare)
Mo Y, Zhang H, Yu X, et al. J Multidiscip Healthc. 2025;18:459–468. Page 461, Ethical Consideration and Data Collection Procedure section, line 2, the text “(No. 2023KYPJ271)” should read “(No. 2024KYPJ142)”. The authors apologize for this error.